ZnSeTe Quantum Dots as an Alternative to InP and Their High-Efficiency Electroluminescence - Lee, Sun-Hyoung; Han, Chang-Yeol; Song, Seung-Won; Jo, Dae-Yeon; Jo, Jung-Ho; Yoon, Suk-Young; Kim, Hyun-Min; Hong, Seung ki; Hwang, Jun Yeon; Yang, Heesun (American Chemical Society, 2020)
Last decade witnessed great advancement in the photoluminescent (PL) quality of visible III-V InP quantum dots (QDs) toward bright, sharp emissivity. Now, InP QDs hold an unrivaled position in the field of next-generation display devices. In an effort to offer non-Cd green QDs as potential alternatives to InP counterparts, in this work, the first viable synthesis of II-VI ternary ZnSeTe QDs is explored. After successful growth of ZnSeTe alloy cores enabled by a balanced precursor reactivity of anions (i.e., Se and Te), sequential triple shells of ZnSe/ZnSeS/ZnS with stepwise type-I energetic potentials are formed. The resulting heterostructured ZnSeTe/ZnSe/ZnSeS/ZnS QDs produce tunable PL wavelengths of 495-532 nm along with high PL quantum yields (QY) of 68-83%, depending on a Te/Se feed molar ratio used for core synthesis. To further evaluate performance of the present ZnSeTe QDs as electroluminescent (EL) emitters, the first fabrication of a solution-processed, multilayered green QD-light-emitting diode (QLED) by adopting Te/Se = 0.28-based triple-shelled QDs with a PL peak of 520 nm and QY of 80% is demonstrated. This device produces promising EL outcomes up to 18 420 cd/m(2) in luminance and 7.6% in external quantum efficiency, outperforming most of green InP QLEDs reported to date.